Effect of a common missense variant in LIPA gene on fatty liver disease and lipid phenotype: New perspectives from a single‐center observational study. Issue 5 (2nd September 2021) - Pasta, Andrea; Borro, Paolo; Cremonini, Anna Laura; Formisano, Elena; Tozzi, Giulia; Cecchi, Stefano; Fresa, Raffaele; Labanca, Sara; Djahandideh, Afscin; Sukkar, Samir Giuseppe; Picciotto, Antonino; Pisciotta, Livia
Abstract: Lysosomal acid lipase deficiency (LAL‐D) is an autosomal recessive disease characterized by hypoalphalipoproteinemia, mixed hyperlipemia, and fatty liver (FL) due to mutations in LIPA se A, lysosomal acid type ( LIPA ) gene. The rs1051338 single‐nucleotide polymorphism (SNP) in LIPA gene, in vitro, could adversely affect the LAL activity (LAL‐A). Nonalcoholic fatty liver disease (NAFLD) is often associated with metabolic syndrome, and the diagnosis requires the exclusion of excess of alcohol intake and other causes of hepatic disease. The aim of the study was to evaluate the impact of rs1051338 rare allele on lipid phenotype, severity of FL, and LAL‐A in patients suffering from dyslipidemia associated with NAFLD. We selected 74 subjects with hypoalphalipoproteinemia or mixed hyperlipemia and evaluated transaminases, liver assessment with controlled attenuation parameter (CAP), LAL‐A, rs1051338 SNP genotype. The presence of rare allele caused higher levels of triglycerides and hepatic transaminase and lower levels of high‐density lipoprotein cholesterol (HDL‐C). Multivariate analysis highlighted independent association between rare allele and FL severity in subjects with NAFLD. The rs1051338 SNP may modulate FL severity and atherogenic dyslipidemia in patients suffering from NAFLD. Abstract : A common polymorphic variant(rs1051338) in LIPA gene has been associated to atherogenic dyslipidemia, metabolic syndrome, obesity, and cardiovascular disease and, in vitro, couldadversely affect the LAL activity. Seventy‐four patients with metabolic riskfactors have been enrolled: higher levels oftriglycerides and hepatic transaminases, and lower levels of high‐densitylipoprotein cholesterol have been observed in patients with the rare allele ofrs1051338 in LIPA gene. The presence of rare polymorphic variant seems to beassociated with severe steatosis in subjects affected by NAFLD.